Intracranial aneurysms: flow analysis of their origin and progression. - Gonzalez, C F; Cho, Y I; Ortega, H V; Moret, J (American Journal of Neuroradiology, 1992)
PURPOSE To explain the origin and growth of intracranial aneurysms using the hemodynamic data obtained from a computer simulation.MATERIALS AND METHODS Pulsatile flow in an intracranial aneurysm cavity was numerically simulated based on physiologic pulsatile flow observed in the aorta. A finite element method was applied to solve the equations of motion and the non-Newtonian viscosity of blood was taken into account in the analysis. An angiogram of a middle cerebral artery segment with aneurysm was used for the computer modeling of blood flow within the aneurysm cavity. Local shear stress and pressure on the wall at the neck of the aneurysm as well as blood flow motions inside the cavity were calculated as a function of time for various stages in the development of the aneurysm.FINDINGS Blood moves into the aneurysm cavity along the proximal wall of the cavity and emerges along the distal wall during the acceleration period of systole; however, during the deceleration period of systole and diastole, blood changes its flow direction, entering along the distal wall of the cavity and leaving along the proximal cavity wall. Rapid changes of blood flow direction result in rapid changes in wall shear stress and pressure at the proximal and distal walls of the cavity, rendering continuous damage to the intima at the cavity neck. These hemodynamic stresses relate to the anatomy of a particular vessel may be responsible for the initiation of aneurysm formation and subsequent progression, thrombosis and/or rupture.CONCLUSION Computer modeling can further our understanding of factors that determine the origin and progression of intracranial aneurysms.